Production of refined and semi-refined carrageenan from red seaweeds a plant design - Bondoc, Gladys Anne F.; Ramos, Johnrich S.; Supan, Marites M.
The purpose of this report is to design a scale-up model of the production of refined and semi-refined carrageenan on a site in Zamboanga City. The process design has been given careful consideration to end up with simple and efficient operation. Detailed estimates of capital costs for the establishment of the plant, revenue income and cost are also give to assess the profitability of the plant. Environmental considerations, safety and quality control description were also provided in the paper.Carrageenan is highly flexible polysaccharide which is extracted from red seaweeds. Its molecular structure has the tendency to curl and form helical structures even at room temperature, giving rise to the formation of a variety of gels. The gelation characteristic of carrageenan is the reason why it is widely used in food and other industries as thickening and stabilizing agents.Commercially, there are three classes of carrageenan considered, the kappa, lambda and iota carrageenan. Kappa- and iota-carrageenan are the most widely used in the food industry as gel-forming agents. These types of carrageenan are extracted from the seaweed species Eucheuma.This species is commercially available as Eucheuma cottonii and Eucheuma spinosum. The Philippines is considered as the largest commercial source of these kinds of seaweeds. The species E. cottonii is chosen as the primary raw material for the process.These seaweed extracts are further classified as refined (RC) and semi-refined (SRC) products. Semi-refined carrageenan differs from the refined variety in the way the carrageenan-content of the seaweeds is processed. In SRC, the carrageenan is not actually extracted from the seaweeds structure. In refined carrageenan, the polysaccharide is dissolved in solution and is the recovered by precipitation. In the proposed design, the two variety of carrageenan will be produced.For refined carrageenan, the processes would be: washing of raw seaweeds, extraction with 1% KOH solution to promote the dissolution of carrageenan into the extract medium, clarification to prevent blinding and creating a porous cake that can easily be recovered, concentration to achieve a greater yield of carrageenan, precipitation with 1 percent KCI solution to form gel, gel-press to give out the gels liquid content, and drying and milling to decrease the liquid content of the carrageenan products and make them into powders. Unlike refined carrageenan processing, semi-refined carrageenan production does not involve the filtration of a carrageenan is solution from the residual solids of the seaweed from which the carrageenan is produced. The SRC method consists of washing the seaweed to remove surface impurities and contaminants, alkaline cooking, washing of the cooked seaweed, drying and finally milling into powder. Aside from its low capital investment, the primary raw materials for carrageenan production are widely available in the country. These include seaweeds, water, KOH, and KCI. Processes are also of minimal number and not too complicated for the operating costs to be high. These specifications make carrageenan production a highly profitable industry.The proposed plant is expected to have a net profit of Php 165 million annually with an estimated time of return of four years. The plant is in operation for 300 days a year with an annual capacity of 3,450 tons, based on the 10% yearly carrageenan demand. This percentage was chosen in order to be safe yet competitive enough in playing the business with giant key holder like Marcell Carrageenan and Shemberg Marketing Corporation, among others. Industrial method of refined and semi-fined carrageenan production is employed. Equipment design and optimization is presented on the latter part of the paper. Cycle time is optimized by using transportable processing baskets for the processing of semi-refined carrageenan. The facility will implement a two-batch operation per carrageenan type. Total processing time for one batch operation is about 10 hours. This would require an 8-hour shifts a day of the employees who will manage the plant operation. Carrageenan production is a burgeoning industry at the present because of its wide variety of applications in different industries such as food, pharmaceutical, and pulp and paper. Carrageenan industry would be also of great help to people living near Zamboanga region, the chosen plant site, for this will generate employment; aside from giving seaweed farmers their additional income. This would make this industry one of the best choices for operation because it encompasses a vast range of industries - with just a single hit for manufacturing the product, carrageenan.